Cover Picture: Reactions in Ionic Liquids (Z. Anorg. Allg. Chem. 1/2017). Issue 1 (January 2017) - Wolff, Alexander; Pallmann, Julia; Brunner, Eike; Doert, Thomas; Ruck, Michael
Abstract : The cover picture symbolizes the halide exchange processes in PX 3 ( X =Cl, Br, I) taking place in ionic liquids. Iodide (yellow) exchanges rapidly with bromide (white) and chloride (blue). Bromide can easily be exchanged by chloride. Chloride neither exchanges with bromide nor with iodide. These observations were made in situ by the application of two spectroscopic techniques, nuclear magnetic resonance and Raman spectroscopy. More details can be found in the article by Alexander Wolff et al on page20 .